2017
DOI: 10.1371/journal.pone.0174675
|View full text |Cite
|
Sign up to set email alerts
|

Signs of current suicidality in men: A systematic review

Abstract: Suicide signs have been identified by expert consensus and are relied on by service providers, community helpers’ and family members to identify suicidal men. Whether signs that are reported in suicide literature accurately describe male presentations of suicidality is unclear. A systematic review of the literature was conducted to identify male-specific signs of current suicidality and identify gaps in the literature for future research. Searches through Medline, CINAHL, PsychInfo and the Behavioral Sciences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…The finding that TCWs rated the male and female caller in each vignette at similar levels of potential suicide risk is consistent with existing studies that have found that similar levels of risk are associated with the same signs of suicide in men and women [ 50 ]. Although emerging research suggests that TCWs may recognize potential for suicide risk through different patterns of suicide signs for male and female callers [ 25 ], the current study suggests that a caller’s gender may not influence TCWs’ perception of the potential suicide risk posed by the caller.…”
Section: Discussionsupporting
confidence: 88%
“…The finding that TCWs rated the male and female caller in each vignette at similar levels of potential suicide risk is consistent with existing studies that have found that similar levels of risk are associated with the same signs of suicide in men and women [ 50 ]. Although emerging research suggests that TCWs may recognize potential for suicide risk through different patterns of suicide signs for male and female callers [ 25 ], the current study suggests that a caller’s gender may not influence TCWs’ perception of the potential suicide risk posed by the caller.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, a narrative description of the data was adopted as a suitable method to meet the review aims [68]. Other narrative studies published in evidence-based journals and databases such as PLoSONE [69] and Cochrane [61], are known to have used the same methodology.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, prior work indicates preparatory behaviors are a marker of heightened risk for suicide. 41,42 Of note, recruiting the 48 patients in our trial required making phone calls to several thousand men (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%